Does the territorial plan of the municipality of Cajicá comply with its objectives? (2017)
At present the municipalities have one the task of orienting and planning the territorial development. For these effects, there are instruments for planning and managing territorial development such as the Development Plan (PD) and the Territorial Planning Plan (POT), which include national, departmental and government policies, Transmit the needs and expectations of the community. The realization of the plans is done in a participatory way between the institutions and the community for a specific purpose that is the welfare of the same that is to organize their territory seeking the social welfare and development of the region. For the punctual topic of Cajicá an analysis of Plan of Ordination is realized, where there are some shortcomings and possible solutions are suggested